Determination of vanadium (V) in drinking water by flow injection and pre-concentration in a knotted reactor by inductively coupled plasma optical emission spectrometry with ultrasonic nebulization - Wuilloud, Rodolfo German (2000)
An on-line vanadium pre-concentration and determination system implemented with inductively coupled plasma optical emission spectroscopy (ICP-OES) associated with a flow injection (FI) method with ultrasonic nebulization (USN) system was studied. The vanadium was retained as vanadium-2-(5-bromo-2-pyridylazo)-5-diethylaminophenol V(V)-(5-Br-PADAP) complex, at pH 3.2. The vanadium complex was removed from the knotted reactor (KR) with 30% v/v nitric acid. A sensitivity enhancement factor of 180 was obtained with respect to ICP-OES using pneumatic nebulization (15 for USN and 12 for KR). The value of detection limit for the pre-concentration of 10 ml of aqueous solution was 19 ng l-1. The precision for 10 replicate determinations at the 5 μg 1-1 V(V) level was 2.6% relative standard deviation (R.S.D.), calculated with the peak heights obtained. The calculation graph using the pre-concentration system for vanadium was linear with a correlation coefficient of 0.9995 at levels near the detection limits up to at least 100 μg l-1. The method was successfully applied to the determination of vanadium in drinking water samples.